Determinants of De Jure: De facto exchange rate regime gaps - Viktar Dudzich (Journal of Central Banking Theory and Practice, 2022)
This paper investigates inconsistencies between countries' official exchange rate regime declarations (the so-called de jure exchange rate regimes) and their actual policy (de facto exchange rate regimes). These exchange rate regime gaps decrease the credibility of monetary policy and are considered an overall negative economic phenomenon. In this paper, I attempt to disclose the determinants of these gaps using the data on several de facto classifications and a wide array of explanatory variables of economic and institutional nature. The results suggest that a number of macroeconomic factors such as foreign exchange reserves, current account balance and economic openness influence the probability of monetary authorities breaking commitment to their official exchange rate regime. At the same time, I also discover that the exchange rate regime gaps are less frequent in more democratic and institutionally advanced countries although the results tend to differ depending on the de facto classification used and the nature of gap (either de jure floating - de facto fixed or de jure fixed - de facto floating).
Keywords: E02; F31; 330; exchange rate regime; de facto exchange rate regime; fixed exchange rate; floating exchange rate